Nigerian former guerrilla journalists ten years into democracy: reformists and revolutionaries (2011)
The question of what happens to activists and resisters after their battle has been lost or won has been asked in many different contexts but answered in a few. In the context of the guerrilla journalists in Nigeria who confronted the military and endured severe brutality in their fight for democracy, that question has not been answered. Ten years after Nigeria returned to democracy, this paper sought to answer that question. Through interviews with nine former guerrilla journalists and an examination of some of their contemporary writings, the paper discovered that the journalists in question were disappointed with the practice of democracy in Nigeria. Their disappointment emanates from their perception that the evils which they fought against during the military era still persist, and that some of the enemies of democracy who allied with the military are the ones paraded as heroes of democracy today while guerrilla journalists pale into oblivion. The disappointment is not helped by the financial and other difficulties facing some of these journalists. They have thus retained some of the old adversarial journalism methods. While some hoped that the Nigerian democracy would stabilise, others thought the solution to the Nigerian problem lay in some drastic events such as a revolution. The paper discusses the implications of this for the practice and study of the media and democracy in Nigeria.